IN GEOLOGICAL AND GEOTECHNICAL PROCESSES IN THE MINE USE OF TECHNOLOGICAL SCANNING EQUIPMENT IN THE UNDERGROUND MINING METHOD (Intent Research Scientific Journal, 2023)
Laser scanning and 3D point cloud data is used extensively in open pit and underground mining operations. Point cloud data generated with laser scanners has improved survey, conformance, and geotechnical process efficiency and has become a key data component for planning, operations and decision-making. The advent of new software tools designed specifically to manage real-time 3D scan data has also improved the accuracy, quality and usability of underground scan data, revolutionising workflows through the industry. In this paper, several case studies will demonstrate the versatility and value of laser scanning in the context of underground operations demonstrating the use of laser scanning and derived point cloud data to improve efficiency, reduce costs and increase the safety of staff and assets across the operation. Laser scanning technology has advanced significantly in terms of mobility and mapping, but there are constraints in coherent and consistent data collection at certain mines due to feature deficiency, dynamics, and environmental influences such as dust and water. Studies suggest that laser scanning has matured over the years for change detection, clearance measurements and structure mapping applications. However, there is scope for improvements in lithology identification, surface parameter measurements, logistic tracking and autonomous navigation. Laser scanning has the potential to provide real-time solutions but the lack of infrastructure in underground mines for data transfer, geodetic networking and processing capacity remain limiting factors. Nevertheless, laser scanners are becoming an integral part of mine automation thanks to their affordability, accuracy and mobility, which should support their widespread usage in years to come.